Mental Health Exploration and Screening in Adults and Elderly Age Groups - Frans Judea Samosir; Victor Trismanjaya Hulu; Hartono; Aida Julpa; Yohana Trisintya Sinurat (CV. Inara, 2022)
Mental health is an issue that is often discussed during the Covid-19 pandemic. It is critical to understand mental health for realizing its beneficial aspects. Early detection or screening of mental health status is an excellent step to prevent mental health problems. The researchers are interested in screening mental health problems in groups of adults and the elderly. This research design is a descriptive study with a cross-sectional data collection approach. The population in this study were all residents on Jalan Pasar VII Padang Bulan, Medan. The research sample was 139 people who were recruited by non-probability sampling with purposive sampling technique. Data collection was carried out from August to December 2021. The questionnaire used in this study is the Depression Anxiety Stress Scales (DASS 42) questionnaire, which is a tool for measuring stress, anxiety, and depression levels which contains 42 questions. This study shows that from 139 respondents, 54 people (38.85) suffer from mental health problems. Types of mental health problems experienced by respondents were stress as much as 32 people (23%), 54 people (38.85%) experienced anxiety, and 36 people experienced depression (25.9%). It is crucial for the community to educate themselves on how to manage their mental health in a healthier way.